2022
DOI: 10.3390/app12041900
|View full text |Cite
|
Sign up to set email alerts
|

Using Simulated Pest Models and Biological Clustering Validation to Improve Zoning Methods in Site-Specific Pest Management

Abstract: Site-specific pest management (SSPM) is a component of precision agriculture that relies on spatially enabled agronomic data to facilitate pest control practices within management zones rather than whole fields. Recent integration of high-resolution environmental data, multivariate clustering algorithms, and species distribution modeling has facilitated the development of a novel approach to SSPM that bases zone delineation on environmentally independent subfield units with individual potential to host pest po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…1a, b). The space-time dynamics of spittlebugs are highly sensitive to environmental conditions (Figueredo et al 2021), which, in the case of the study area, have been found to be highly associated with transitions from dry to rainy periods (Ramirez-Gil et al 2021), which sets the stage for coupling population dynamics and associated environmental factors to develop early warning systems (Méndez-Vázquez et al 2019;L. Méndez-Vázquez et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…1a, b). The space-time dynamics of spittlebugs are highly sensitive to environmental conditions (Figueredo et al 2021), which, in the case of the study area, have been found to be highly associated with transitions from dry to rainy periods (Ramirez-Gil et al 2021), which sets the stage for coupling population dynamics and associated environmental factors to develop early warning systems (Méndez-Vázquez et al 2019;L. Méndez-Vázquez et al 2022).…”
Section: Discussionmentioning
confidence: 99%